BLOEM: A spatially explicit model of bioenergy and carbon capture and storage, applied to Brazil. Issue 2 (8th December 2022) - Tagomori, Isabela; Daioglou, Vassilis; Rochedo, Pedro; Angelkorte, Gerd; Schaeffer, Roberto; van Vuuren, Detlef; Szklo, Alexandre
Abstract: Bioenergy could play a major role in decarbonizing energy systems in the context of the Paris Agreement. Large‐scale bioenergy deployment could be related to sustainability issues and requires major infrastructure investments. It, therefore, needs to be studied carefully. The Bioenergy and Land Optimization Spatially Explicit Model (BLOEM) presented here allows for assessing different bioenergy pathways while encompassing various dimensions that influence their optimal deployment. In this study, BLOEM was applied to the Brazilian context by coupling it with the Brazilian Land Use and Energy Systems (BLUES) model. This allowed investigating the most cost‐effective ways of attending future bioenergy supply projections and studying the role of recovered degraded pasture lands in improving land availability in a sustainable and competitive manner. The results show optimizing for limiting deforestation and minimizing logistics costs results in different outcomes. It also indicates that recovering degraded pasture lands is attractive from both logistics and climate perspectives. The systemic approach of BLOEM provides spatial results, highlighting the trade‐offs between crop allocation, land use and the logistics dynamics between production, conversion, and demand, providing valuable insights for regional and national climate policy design. This makes it a useful tool for mapping sustainable bioenergy value chain pathways. Abstract : Bioenergy could play a major role in decarbonizing energy systems. However, its large‐scale deployment could be related to sustainability issues and major infrastructure investments. In this study, we present the Bioenergy and Land Optimization Spatially Explicit Model (BLOEM), applied to Brazil. We investigate cost‐effective ways of attending future bioenergy supply projections and the role of recovered degraded pasture lands in improving land availability in Brazil, in a sustainable and competitive manner. The results show optimizing for limiting deforestation and minimizing logistics costs results in different outcomes and indicate that recovering degraded pasture lands is attractive from both logistics and climate perspectives.